Synthesis and characterization of copper selenide and tin selenide powders by mechanical alloying method - Loh, Yen Nee; Talib, Zainal Abidin; Zainal, Zulkarnain; Liew, Josephine Ying Chyi (Scientific.Net, 2021)
This paper reports on the synthesis of copper selenide (CuSe) and tin selenide (SnSe) powders by high energy planetary ball milling, starting from elemental powders. Synthesis time and milling speed have been optimized to produce single phase CuSe and SnSe materials. The structural, compositional, morphological and optical properties of the synthesized samples have been analyzed by X-ray diffraction (XRD), transmission electron microscopy (TEM), Field Emission Scanning Electron Microscopy (FESEM) and UV-Vis. The low-temperature phase selection of the binary compound in this system is seen as a direct consequence of the thermodynamic facilitation, coupled with the capability of mechano-chemical synthesis to aid in overcoming kinetic constraints.